A pobreza na Bahia sob o prisma multidimensional: uma análise baseada na abordagem das necessidades básicas e na abordagem das capacitações - Lacerda, Fernanda Calasans Costa (2009)
This dissertation examines poverty in the state of Bahia under the multidimensional approach to the study of poverty, emphasizing the need to enlarge the focus of research beyond the lack of income and to consider the multidimensionality of poverty in developing policies that aim to combat it. Initially, discuss, the evolutionary path of the study of poverty, emphasizing the dominance of unidimensional monetary approach in the work on poverty in Brazil and Bahia. Subsequently, performs an empirical analysis of poverty in Bahia in 1995, 2001 and 2006, based on two approaches to study of multidimensional poverty: the basic needs approach and the capabilities approach. From the concepts employed by these approaches, defines poverty as the dissatisfaction of basic human needs which deprives the individual to develop and expand its capabilities. The methodology used in the empirical analysis is to apply the multivariate method of the Multiple Correspondence Analysis in the calculation of a multidimensional indicator of poverty (IMP) per unit of population studied. This indicator is composed of a set of qualitative variables, called the primary indicators of deprivation. The results of applying this method also allow for a multidimensional poverty line, used as a criterion for identification of poverty. Based on this poverty line and the indicator, was possible to calculate the traditional indices of poverty FGT (0), FGT (1) and FGT (2) and then measure the poverty in Bahia. The results show that the proportion of poor people was high, especially among the rural population, but this proportion decreased between 1995 and 2006, except in the metropolitan area. Among the individuals considered poor, poverty was more intense and more severe in rural areas. The decomposition of poverty by race and color or by type of family indicated that individuals in black or brown, and the families of the "mother with children under 14 years", had higher risk of poverty. The breakdown by sex showed no significant differences between men and women regarding the extent and risk of poverty. Regarding census areas, the less populous municipalities were those that had a higher percentage of poor. When compared with the income poverty, the multidimensional poverty is had higher (years 2001 and 2006) and stable. While this first there was a significant fall in the period 1995/2006, the decline occurred in the second was much less significant. Thus, by focusing the analysis only on the inadequacy of income, it is not possible to investigate other types of deprivation that affect the people of Bahia. Although in the period examined to identify improvements in the primary indicators, living conditions these people were still short of what could be considered a adequate situation, revealing that a significant population of Bahia had not their basic needs met. Moreover, the set of deprivation cannot be disregarded in the planning and implementation of policies to combat poverty, because, otherwise, it undermines the effectiveness of such policies.